2007
DOI: 10.2193/2006-146
|View full text |Cite
|
Sign up to set email alerts
|

Demographics of Black Vultures in North Carolina

Abstract: : Understanding the contributions of vital rates to species population growth is critical to developing new management protocols. We constructed a model population for black vultures (Coragyps atratus) in North Carolina, USA, based on demographic data from a 14‐year study. The model population was similar in stage structure to the reference population, and adult survival was the primary contributor to the annual rate of increase (10.6%). We suggest that the North Carolina black vulture population is experienci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 18 publications
0
12
0
Order By: Relevance
“…4) bounds the possible values for this growth rate, although we suspect we overstated uncertainty at the low ends of the parameter estimates. We note that the matrix model developed by Blackwell et al (2007), and based on the same data sources, produced an estimate of population growth for the North Carolina black vulture population of 10.6% annually (and also demonstrated the marked sensitivity of this growth rate to the estimate of ad survival rate). Our belief, therefore, is that the median estimate for r max (10.6%) is the best to work with at this time, although it is likely conservative.…”
Section: Scientific Considerationsmentioning
confidence: 72%
See 2 more Smart Citations
“…4) bounds the possible values for this growth rate, although we suspect we overstated uncertainty at the low ends of the parameter estimates. We note that the matrix model developed by Blackwell et al (2007), and based on the same data sources, produced an estimate of population growth for the North Carolina black vulture population of 10.6% annually (and also demonstrated the marked sensitivity of this growth rate to the estimate of ad survival rate). Our belief, therefore, is that the median estimate for r max (10.6%) is the best to work with at this time, although it is likely conservative.…”
Section: Scientific Considerationsmentioning
confidence: 72%
“…Black vultures, like other New and Old World vultures, exhibit delayed onset of sexual maturity. Blackwell et al (2007) demonstrated via a stage-structured matrix model that age-at-first-breeding must be closer to 5 years than to 8 years (the sole record for a known-age black vulture; Parker et al 1995). Age-at-first-breeding is typically 4 years in griffon vultures (Blanco andMartinez 1996, Sarrazin et al 1996) and 4-6 years in Cape vultures (Gyps coprotheres; Robertson 1984).…”
Section: Demography Of Black Vulturesmentioning
confidence: 99%
See 1 more Smart Citation
“…2) Another example is that of the black vulture Coragyps atratus , whose population is thriving and is currently estimated at 20 million individuals (Rich et al 2004, Blackwell et al 2007, Carrete et al 2009); it now constitutes the most abundant of the seven species of New World vultures (i.e. Cathartidae).…”
Section: Native Versus Non-native Species: An Inappropriate Dichotomymentioning
confidence: 99%
“…Also, air carriers recently have replaced four-engine aircraft with two-engine designs that markedly reduce the noise of their predecessors, which is suspected to reduce the distance at which animals can detect and react to aircraft (Solman, 1976;Kelly et al, 2001;Kelly and Allan, 2006). Another factor contributing to the observed increase in bird strikes is population growth of some species (e.g., Rusch et al, 1995;Waller and Alverson, 1997;Blackwell et al, 2007), especially larger animals (>2 kg) that present substantial hazards to aviation safety (Dolbeer et al, 2000;Dolbeer and Eschenfelder, 2002;.…”
Section: Introductionmentioning
confidence: 99%